2019
DOI: 10.3390/ma12193261
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Fatigue Performance of Steel Fiber Reinforced Expanded-Shales Lightweight Concrete Superposed Beams with Initial Static-Load Cracks

Abstract: Concerning the structural applications of steel fiber reinforced expanded-shales lightweight concrete (SFRELC), the present study focuses on the flexural fatigue performance of SFRELC superposed beams with initial static-load cracks. Nine SFRELC superposed beams were fabricated with the SFRELC depth varying from 50% to 70% of the whole sectional depth, and the volume fraction of steel fiber ranged from 0.8% to 1.6%. The fatigue load exerted on the beams was a constant amplitude sinusoid with a frequency of 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…To simplify the computation, the beneficial effect of stirrups on shear cracking resistance can be considered as a reliability reserve. The same formula can be used for predicting the shear-cracking force of reinforced SFRELC beams with or without web reinforcement [10], Table 2 presents the calculated values of V cr by using Formula (9). Based on the statistical analysis, the average of ratios of test to calculation results is 1.034 with the coefficient of variation as 0.027.…”
Section: Shear-cracking Forcementioning
confidence: 99%
See 1 more Smart Citation
“…To simplify the computation, the beneficial effect of stirrups on shear cracking resistance can be considered as a reliability reserve. The same formula can be used for predicting the shear-cracking force of reinforced SFRELC beams with or without web reinforcement [10], Table 2 presents the calculated values of V cr by using Formula (9). Based on the statistical analysis, the average of ratios of test to calculation results is 1.034 with the coefficient of variation as 0.027.…”
Section: Shear-cracking Forcementioning
confidence: 99%
“…The studies on the flexural behavior of reinforced SFRELC beams under static concentrated loads indicated that the cracking moment, flexural stiffness, and bearing capacity as well as ductility are effectively promoted with the increasing volume fraction of steel fibers from 0.4% to 1.6%, and the crack growth is confined with decreased spacing and width [ 6 , 7 , 8 ]. A fatigue life of reinforced SFRELC superposed beams with ductile failure mode was prolonged by preventing fatigue fracture of longitudinal tensile rebar and reducing crack growth, and the failure could be expected with the trend curves of fatigue flexural stiffness [ 9 ]. By the experimental study on shear-cracking force and shear crack extension, mid-span deflection, shear failure mode, and shear capacity, the effective enhancement of steel fibers was confirmed on the shear behavior of reinforced SFRELC beams without stirrups; however, the brittle failure could not be prevented with the rupture of expanded shales along diagonal cracks [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in steel-fiber-reinforced concrete include the development of steel-fiberreinforced expanded-shale lightweight concrete (SFRELC) [3]. In particular, the authors explored the fatigue strength of composite SFRELC-RC beams through experiments.…”
mentioning
confidence: 99%
“…Advances in steel-fiber-reinforced concrete include the development of steel-fiber-reinforced expanded-shale lightweight concrete (SFRELC) [ 3 ]. In particular, the authors explored the fatigue strength of composite SFRELC-RC beams through experiments.…”
mentioning
confidence: 99%